Message from the Editor-in-Chief Vol.1(1) - Shrestha, Surendra Man (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
It gives me great pleasure to publish first issue of journal of NSPOI. We intended to publish case reports, review articles, with main focus on original research articles. Our objective is to reach all the clinical practitioners, who have knowledge and interest but have lack of time to record the interesting cases, research activities and new innovative procedures which help us in updating our knowledge and improving our treatment. Our main emphasis is to promote scientific papers of good quality and we extend our boundaries right from periodontal care to allied sciences. We feel that there is a wide scope to explore various fields of dental sciences. With clear intentions we welcome you to post comments related to the journal by sparing your valuable time and request you to send articles. Finally, I thank my editorial team, technical team, authors and well wishers, who are promoting this journal. I specially thank the president of NSPOI, Dr Shaili Pradhan who has trusted me and given this responsibility. With these words, I conclude with thanks to Dr. Bhageshwar Dhami, Executive editor for his continuous effort to publish this journal. Prof. Dr. Surendra Man Shrestha JNSPOI Editor-in-Chief